Targeting for pollutant reductions in the Great Barrier Reef river catchments. Issue 89 (November 2018) - Star, Megan; Rolfe, John; McCosker, Kevin; Smith, Rachael; Ellis, Robin; Waters, David; Waterhouse, Jane
Highlights: Pollutant reductions are needed to improve water quality to the Great Barrier Reef. Drivers of pollutant reductions are varied and diverse across large catchments. Integrating spatial, marine, participation and cost information helps predict reductions at a finer scale across the Great Barrier Reef catchments. Using spatial data enables prioritisation of locations, industries and priority actions. Abstract: The declining health of the Great Barrier Reef (GBR) from poor water quality has increased the urgency for pollutant reductions at the same time that available financial resources and knowledge regarding the most appropriate interventions are limited. Prioritisation of water quality interventions in the Great Barrier Reef catchments is the process of identifying which land based actions can achieve the largest environmental benefits at the lowest cost. For prioritisation to be effective a focus is required on the outcomes of pollution reduction activities as compared to the inputs. In this paper we set out a framework for prioritising actions to improve water quality into the Great Barrier Reef, as well as providing a case study analysis using 47 individual river basins across the six large scale catchments, three pollutants and two industries. The results identify the most cost-effective options for water quality improvements aligning to locations of medium risk to reef health. The outcomes of the analysis highlight the importance of seeking pollutant reductions where the most effective outcome can be achieved rather than simply targeting an industry or a catchment.